2018
DOI: 10.1093/infdis/jiy712
|View full text |Cite
|
Sign up to set email alerts
|

Remembering the Host in Tuberculosis Drug Development

Abstract: New therapeutics to augment current approaches and shorten treatment duration are of critical importance for combating tuberculosis (TB), especially those with novel mechanisms of action to counter the emergence of drug-resistant TB. Host-directed therapy (HDT) offers a novel strategy with mechanisms that include activating immune defense mechanisms or ameliorating tissue damage. These and related concepts will be discussed along with issues that emerged from the workshop organized by the Stop TB Working Group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 52 publications
(55 reference statements)
1
36
0
Order By: Relevance
“…Despite the availability of effective antimicrobial agents, patients with TB meningitis remain at risk for paradoxical worsening on therapy (labeled immune reconstitution inflammatory syndrome [IRIS] in HIV+ patients) [ 36 ] and severe complications such as vasculitis leading to ischemic stroke, which may be driven by a pathologic immune response [ 37 ]. Consequently, there has been considerable interest in the use of adjunctive host-directed therapies in tuberculosis [ 38 ]. Corticosteroids have been shown to improve mortality [ 13 ], whereas aspirin may reduce the risk of stroke [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the availability of effective antimicrobial agents, patients with TB meningitis remain at risk for paradoxical worsening on therapy (labeled immune reconstitution inflammatory syndrome [IRIS] in HIV+ patients) [ 36 ] and severe complications such as vasculitis leading to ischemic stroke, which may be driven by a pathologic immune response [ 37 ]. Consequently, there has been considerable interest in the use of adjunctive host-directed therapies in tuberculosis [ 38 ]. Corticosteroids have been shown to improve mortality [ 13 ], whereas aspirin may reduce the risk of stroke [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Host-directed therapies have emerged as a novel and promising approach to treat TB, whose modulation of host response is likely to avoid the development of bacterial resistance [165,166]. Unlike conventional antibiotics aimed at targeting the bacteria, host-directed therapy aims at targeting the host immune response either by directly boosting its ability to effectively eliminate the bacterial load or reduce the lung damage associated with granulomatous disease.…”
Section: Future Prospectsmentioning
confidence: 99%
“…He concluded that there are major differences in the quality of T-cell polarization between mice and primates, leading to major differences in function and migration. P. Karakousis showed interest in host-directed therapies (HDT) for TB since Mtb is known to subvert host responses and induce lung damage [39,40]. Preclinical endpoints of HDT include the assessment of bacterial clearance in the host and histological or radiographic assessment of lung inflammation.…”
Section: Barber Studied T Cell Migration/differentiation and Spatimentioning
confidence: 99%